Moral distress among intensive care unit professions in the UK: a mixed-methods study - Joyce Yeung; Christopher Bassford; Anne-Marie Slowther; Adam Jonathan Boulton (BMJ Open, 2023)
Objective To assess the experience of moral distress among intensive care unit (ICU) professionals in the UK.Design Mixed methods: validated quantitative measure of moral distress followed by purposive sample of respondents who underwent semistructured interviews.Setting Four ICUs of varying sizes and specialty facilities.Participants Healthcare professionals working in ICU.Results 227 questionnaires were returned and 15 interviews performed. Moral distress occurred across all ICUs and professional demographics. It was most commonly related to providing care perceived as futile or against the patient’s wishes/interests, followed by resource constraints compromising care. Moral distress score was independently influenced by profession (p=0.02) (nurses 117.0 vs doctors 78.0). A lack of agency was central to moral distress and its negative experience could lead to withdrawal from engaging with patients/families. One-third indicated their intention to leave their current post due to moral distress and this was greater among nurses than doctors (37.0% vs 15.0%). Moral distress was independently associated with an intention to leave their current post (p<0.0001) and a previous post (p=0.001). Participants described a range of individualised coping strategies tailored to the situations faced. The most common and highly valued strategies were informal and relied on working within a supportive environment along with a close-knit team, although participants acknowledged there was a role for structured and formalised intervention.Conclusions Moral distress is widespread among UK ICU professionals and can have an important negative impact on patient care, professional wellbeing and staff retention, a particularly concerning finding as this study was performed prior to the COVID-19 pandemic. Moral distress due to resource-related issues is more severe than comparable studies in North America. Interventions to support professionals should recognise the individualistic nature of coping with moral distress. The value of close-knit teams and supportive environments has implications for how intensive care services are organised.